Cyclic Guanidine Compounds from Toxic Newts Support the Hypothesis that Tetrodotoxin is Derived from a Monoterpene. (1st June 2016) - Kudo, Yuta; Yasumoto, Takeshi; Mebs, Dietrich; Cho, Yuko; Konoki, Keiichi; Yotsu‐Yamashita, Mari
Abstract: The biosynthesis of tetrodotoxin (TTX), a potent neurotoxin consisting of a 2, 4‐dioxaadamantane skeleton and a guanidine moiety, is an unsolved problem in natural product chemistry. Recently, the first C5–C10 directly bonded TTX analogue, 4, 9‐anhydro‐10‐hemiketal‐5‐deoxyTTX, was obtained from toxic newts and its carbon skeleton suggested a possible monoterpene origin. On the basis of this hypothesis, screening of predicted biosynthetic intermediates of TTX was performed using two MS‐guided methods. Herein, five novel cyclic guanidine compounds from toxic newts are reported which commonly contain a cis ‐fused bicyclic structure including a six‐membered cyclic guanidine. These structures could be biosynthetically derived from geranyl guanidine through oxidation, cyclization, and/or isomerization steps. LC–MS analysis confirmed the widespread distribution of the five novel compounds in toxic newt species. These results support the hypothesis that TTX is derived from a monoterpene.